2023
DOI: 10.1371/journal.ppat.1011189
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infection promotes tumorigenesis of colorectal cancer via regulating CDC42 acetylation

Abstract: Increasing evidence highlights the role of bacteria in promoting tumorigenesis. The underlying mechanisms may be diverse and remain poorly understood. Here, we report that Salmonella infection leads to extensive de/acetylation changes in host cell proteins. The acetylation of mammalian cell division cycle 42 (CDC42), a member of the Rho family of GTPases involved in many crucial signaling pathways in cancer cells, is drastically reduced after bacterial infection. CDC42 is deacetylated by SIRT2 and acetylated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…In addition to conventional endocytosis, there exist other noncanonical pathways through which cell can leverage to internalize nanomaterials independent of clathrin and caveolin. , Two representative pathways, namely, the clathrin-independent carriers-glycosylphosphotidylinositol-anchored protein enriched compartments (CLIC-GEEC) and fast endophilin-mediated endocytosis (FEME), have been identified and may play crucial roles in the uptake of nanoparticles. We first investigated the distribution profiles of key regulators in CLIC-GEEC and FEME processes, namely, Cdc42, Arf6, and endophilin, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to conventional endocytosis, there exist other noncanonical pathways through which cell can leverage to internalize nanomaterials independent of clathrin and caveolin. , Two representative pathways, namely, the clathrin-independent carriers-glycosylphosphotidylinositol-anchored protein enriched compartments (CLIC-GEEC) and fast endophilin-mediated endocytosis (FEME), have been identified and may play crucial roles in the uptake of nanoparticles. We first investigated the distribution profiles of key regulators in CLIC-GEEC and FEME processes, namely, Cdc42, Arf6, and endophilin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As such, actin network can assemble at the cell cortex, serving a critical role in cellular uptake of substances through CLIC-GEEC. Wang et al reported 41 that the subcellular traffic of Cdc42 to cell cortex is crucial for its role as a cytoskeleton modulator. Our results further prove that fine-tuning of ligand mobility, without changing the nanoparticles of choice, holds the promise of conveniently inducing Cdc42-mediated CLIC-GEEC.…”
Section: Resultsmentioning
confidence: 99%
“…PKCα is an upstream regulator of JNK and promotes its recruitment to cellular membranes ( 94 102 ). Cdc42 is also as an upstream activator of JNK ( 11 , 103 106 ). PKCα and JNK regulate phosphorylation of GRASP55 and GRASP65, respectively ( 19 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 22, 2024. ; https://doi.org/10.1101/2024.03.21.586086 doi: bioRxiv preprint processes, including cell division, intracellular transport, gene transcription, cell cycle regulation, and regulates cell growth and stability. [29][30][31] We overexpressed miR-206 within VEGFA-treated BM-MSCs to detect the expression levels of CDC42 gene and protein in the cells. It was found that the expression of CDC42 was down-regulated in cells transfected with miR-206.…”
Section: Discussionmentioning
confidence: 99%